Pedagogical trends of undergraduate programs in Administering Federal Institutions of Higher Education - Colpo, Iliane; Weise, Andreas Dittmar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The business landscape was significantly changed with the age of the Industrial Revolution, and in the late twentieth century driven by the impacts of Information Technology (IT) and the advent of globalization started a new transformation: the Knowledge Age, where this becomes a valuable resource and often essential, in company management in order to ensure success and even stay in the same market. Educational institutions represent a key role in this process, being responsible for transmitting and or construction of knowledge in this sense is necessary to know the pedagogical trends that guide the teaching-learning process. This work through an exploratory qualitative research aims to identify the pedagogical trends of undergraduate courses in administration in Federal Institutions of Higher Education - IFES, which received the highest rating in the National Higher Education Examination - ENADE. It is used for analysis purposes and the objectives or profile of graduates from each institution. The results show that 54% of the institutions surveyed have progressive pedagogical trends.